The School Principal’s Strategy In Developing Student Competencies At Sdi Darussalam Sumberbaru Jember - nurul iflaha (Mudir : Jurnal Manajemen Pendidikan, 2024)
Student is a subject in education who need guidance and guidance to gain knowledge through the educational process, so that they can become better human beings. The quality of students can be seen from the competencies they possess. The school principal as a leader has an important role in developing student competencies. Strategies are needed by school principals to implement educational activities to increase the work productivity of school residents, develop and increase the competence of students so that they become quality graduates. The method used is descriptive qualitative with interactive model data analysis techniques. The results of the research show that the principal's strategy at SDI Darussalam Sumberbaru Jember is to increase students' competence by adding activities outside of class hours, namely familiarizing (intensive) reading of English and Arabic vocabulary and arranging words into sentences. This activity is carried out every time before learning in class begins. The next strategy is to give assignments to teachers by forming teams so that they can carry out intensive additional activities optimally, as well as evaluating directly so that they can provide input to the teachers on duty so that the activities run optimally.